1994
DOI: 10.3109/10408449409020138
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Metabolic Fate of Styrene

Abstract: Styrene and styrene oxide have been implicated as reproductive toxicants, neurotoxicants, or carcinogens in vivo or in vitro. The use of these chemicals in the manufacture of plastics and polymers and in the boat-building industry has raised concerns related to the risk associated with human exposure. This review describes the literature to date on the metabolic fate of styrene and styrene oxide in laboratory animals and in humans. Many studies have been conducted to assess the metabolic fate of styrene in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(70 citation statements)
references
References 72 publications
1
69
0
Order By: Relevance
“…The exposure (Miller et al, 1994), toxicologic (McConnell and Swenberg, 1994;Phillips and Farmer, 1994;Scott and Preston, 1994), metabolic (Sumner and Fennell, 1994), and epidemiologic (Rebert and Hall, 1994;Coggon, 1994) data on styrene were recently reviewed. Several chronic toxicity/carcinogenicity studies of styrene in laboratory animals were performed in the 1970s, but most are deficient for use in human health hazard assessments due to problems in study design, conduct, or reporting (McConnell and Swenberg, 1994); problems included exceeding the Maximum-tolerated-dose, intercurrent disease, and minimal descriptions of the conduct and detailed results of the studies.…”
mentioning
confidence: 99%
“…The exposure (Miller et al, 1994), toxicologic (McConnell and Swenberg, 1994;Phillips and Farmer, 1994;Scott and Preston, 1994), metabolic (Sumner and Fennell, 1994), and epidemiologic (Rebert and Hall, 1994;Coggon, 1994) data on styrene were recently reviewed. Several chronic toxicity/carcinogenicity studies of styrene in laboratory animals were performed in the 1970s, but most are deficient for use in human health hazard assessments due to problems in study design, conduct, or reporting (McConnell and Swenberg, 1994); problems included exceeding the Maximum-tolerated-dose, intercurrent disease, and minimal descriptions of the conduct and detailed results of the studies.…”
mentioning
confidence: 99%
“…These metabolites were also detected in urine of workers in reinforced plastic plants (Pfäffli et al, 1981;Manini et al, 2003). 2-Vinylphenol (2-VP) and 3-vinylphenol (3-VP) have been proposed as aromatic hydroxylation products of styrene (Sumner and Fennell, 1994), but they have never been identified either in experimental animals or in humans exposed to styrene. Most recently, Linhart et al (2010) reported urinary 3-VP, 4-VP, and possible 2-VP in mice exposed to airborne styrene.…”
Section: Introductionmentioning
confidence: 99%
“…Lung microsomal incubations with styrene afforded a similar metabolite profile except for vinyl-1,4-hydroquinone and 4-hydroxystyrene glycol. The observation of the glycols infers the formation of the corresponding epoxides (Bond, 1989;Sumner and Fennell, 1994). The observed vinyl-1,4-hydroquinone may be spontaneously oxidized to vinyl-1,4-benzoquinone (Scheme 2) (Shen et al, 1997).…”
Section: Phenolic Metabolites Of Styrenementioning
confidence: 99%
See 2 more Smart Citations